Music Listening Habits and Music Perception Abilities of Prelingually Deafened Adolescent Cochlear Implant Recipients - Yüksel, Mustafa; Atılgan, Atılım; Çiprut, Ayça (Journal of the American Academy of Audiology, 2020)
Background Music is a very important art form that can evoke strong emotions and involvement with it can have a considerable impact on cochlear implant (CI) recipients' quality of life. It is well known that music perception is limited in CI with fully electric hearing and CI recipients have significantly poorer music-appraisal ability when compared with normal hearing subjects. Considering the importance of music on the life of an adolescent and negative impact of hearing loss on mental health, understanding and improving music listening habits and perception abilities can have a positive impact on the mental health of CI user adolescents.Purpose This study aims to evaluate music listening habits and music perception abilities of prelingually deafened adolescent CI users to reveal the relationship between self-reported assessment and psychophysical measurement.Research Design The psychophysical measures of music perception and self-reported music listening habits of adolescent CI users were obtained.Study Sample Twenty-nine prelingually deafened adolescent CI users were evaluated in this study.Data Collection and Analysis The Turkish Clinical Assessment of Music Perception (T-CAMP) test was used to evaluate music perception abilities. These abilities were evaluated with a three-item questionnaire assessing enjoyment of music, listening habits, and comprehension of lyrics. Pearson's correlation coefficients were calculated to assess the relationship between the T-CAMP subtests and questionnaire items.Results Statistically significant correlations were observed between the melody-recognition subtest of T-CAMP and all three questionnaire items. The correlation between the enjoyment and rate items on the questionnaire was also statistically significant.Conclusion The present study shows that adolescent CI users also enjoy and listen to music in ways similar to postlingually deafened adult CI users. It also demonstrates that melody-recognition abilities have a significant relationship with music enjoyment and listening habits in prelingually deafened adolescent CI users.
Keywords: cochlear implants; music perception; listening habits; adolescent